Mathematical modeling based on exergy analysis for a bagasse boiler (2017)
In the methodology proposed for this work an exergy analysis of a modern bagasse boiler, which operates as the main equipment of a cogeneration plant of 34 MW of a sugar mill north of the department of Valle del Cauca (Colombia) is performed. In this analysis the boiler is divided into seven blocks or functional units, which have their own operating conditions linked to the performance of the steam generator. Second Law balances can estimate the irreversibility in each of the defined blocks and, when added together these, total losses and exergy efficiency in the steam generator are obtained. The mathematical model developed allows, among other things, collating the values of temperatures of combustion gases through each heat exchange equipment from the actual data boiler. In addition, together with exergy analysis, the model allows a parallel with energy analysis. In this model, an important relationship with continuous boiler blowdown found. This is directly related to the quality of feed water and boiler operation, if these values come out of defined control, a considerable loss of efficiency occurs